Determinação do momento fletor resistente à flambagem lateral com torção de vigas de aço casteladas - Eduardo Matos Bezerra (2011)
Castellated steel beams are fabricated from standard hot-rolled I-sections and have many advantages including greater bending rigidity, economic construction, ease of services through the web openings and good aesthetic appearance. However, the castellation of beams results in different failures modes that depending on geometry of beam, size of web openings and type of loading and lateral restraints conditions.In this work, a procedure for determination of nominal resistance to bending moment for castellated steel beams, considering the Peiner and the anglo-saxon patterns, for lateral torsional buckling limit state is proposed. The beams are submitted to uniform bending, uniform distributed and loading and concentrated load and the twistingrotations at beam ends are prevented and the warping displacements are released. To get this procedure a numerical analysis was elaborated and validated, that considers the nonlinear response of the material, the residual stresses and geometrical nonlinear behavior of the structure, using ABAQUS. The results of the numerical analysis are compared to results obtained for similar plain web and real profile using brazilian code NBR 8800:2008. The results are also compared to results obtained using the procedures of brazilian code considering the geometrical properties of the net section in the center of the holes of castellated beams. All this comparisons have the purpose to get a practical and easy procedure for determination of nominal resistance for castellated steel beams. The results are also compared to standard EN 1993-1-1:2005.